2022
DOI: 10.1111/epi.17260
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive phenotypes in frontal lobe epilepsy

Abstract: Objective: Neuropsychological profiles are heterogeneous both across and within epilepsy syndromes, but especially in frontal lobe epilepsy (FLE), which has complex semiology and epileptogenicity. This study aimed to characterize the cognitive heterogeneity within FLE by identifying cognitive phenotypes and determining their demographic and clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Furthermore, the visuospatial domain was the least impaired across a sample of 2485 patients with drug-resistant TLE and only 1–2% of the single-domain phenotype had an isolated visuospatial impairment. Regarding visual memory, studies that have included visual memory tests 10 , 18 , 37 , 60 have combined verbal and visual memory tests into one domain and it remains to be determined if an isolated visual memory phenotype exists. A recent meta-analysis explored the lateralizing capabilities of non-verbal memory tests in patients with unilateral TLE and noted that the stimulus type (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the visuospatial domain was the least impaired across a sample of 2485 patients with drug-resistant TLE and only 1–2% of the single-domain phenotype had an isolated visuospatial impairment. Regarding visual memory, studies that have included visual memory tests 10 , 18 , 37 , 60 have combined verbal and visual memory tests into one domain and it remains to be determined if an isolated visual memory phenotype exists. A recent meta-analysis explored the lateralizing capabilities of non-verbal memory tests in patients with unilateral TLE and noted that the stimulus type (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…32 Across all our participants, however, both letter fluency and similarities had higher correlations with language than with executive function measures (Supplementary Methods), and were thus considered as language measures. 33…”
Section: Methodsmentioning
confidence: 99%
“…In efforts to better understand this heterogeneity, investigations have focused on identifying patterns of cognitive deficits or cognitive phenotypes 9 . Across studies in focal epilepsy, three to four phenotypes have been identified with stable and reproducible cognitive patterns, including a group with generalized impairment, a group with focal deficits, and a third group with intact profiles 9–18 . This phenotype approach has proven useful for establishing links between distinct neural abnormalities and patterns of cognitive impairment 11,12,14,16 and predicting cognitive progression 10 and postoperative outcomes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Across studies in focal epilepsy, three to four phenotypes have been identified with stable and reproducible cognitive patterns, including a group with generalized impairment, a group with focal deficits, and a third group with intact profiles. [9][10][11][12][13][14][15][16][17][18] This phenotype approach has proven useful for establishing links between distinct neural abnormalities and patterns of cognitive impairment 11,12,14,16 and predicting cognitive progression 10 and postoperative outcomes. 18 Despite an extensive literature focused on the neuropsychological syndromes of the epilepsies and the recent advances in cognitive phenotyping, there are no evidence-based criteria for guiding cognitive diagnostics in epilepsy research.…”
Section: Introductionmentioning
confidence: 99%